The UN role during the peace transition in Colombia: 2015-2019 - Montoya, Carlos; Sánchez, Fabio (Estudios Internacionales, 2023)
How effective is UN assistance in post-conflict societies? This paper evaluates the performance of the United Nations Development Assistance Framework (UNDAF) in Colombia during the period 2015-2019. The programmatic agenda in relation to the construction of peace and sustainable development is analyzed. The evidence shows a positive impact, despite certain weaknesses in the degree of efficacy. All of this, in the midst of a complex sociopolitical scenario in the construction of peace.